An electrical equivalent circuit to simulate the output power of an AlGaAs/GaAs planar gunn diode oscillator. Issue 9 (11th August 2018) - Maricar, Mohamed Ismaeel; Khalid, Ata; Dunn, Geoff; Greedy, Steve; Thomas, Dave; Cumming, David R. S.; Oxley, Chris H.
Abstract: The planar Gunn diode offers the potential of microwave, milli‐metric and THz‐based oscillators, which can be fabricated as part of a microwave monolithic integrated circuit (mmic). The paper develops an electrical representation of an aluminum gallium arsenide (AlGaAs) based planar Gunn diode with an active channel length of approximately 4 μm and width of 120 μm, embedded in an oscillator circuit. The work indicates a maximum simulated RF output power of +5 dBm compared with published experimental results of −19 dBm for similar diodes.